Pengaruh Pemberian Pelatihan Safety Behavior terhadap Perubahan Tingkat Pengetahuan dan Sikap Tenaga Kerja Sektor Informal - ulfah, nur; aji, budi; harwanti, siti (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2024)
ABSTRACT Background: Work accidents are an occupational safety and health problem. Safety behavior can increase safety, productivity, reduce work accidents and improve worker welfare. Training can help workers in the informal sector in implementing safety behavior. Methodology: Service is carried out using counseling methods to informal sector workers consisting of false eyelash workers, exhaust workers, sand miners, cracker industry home workers and street vendors. The number of participants who attended was 100% with a total of 50 people. The assessment instrument uses pre and post test sheets. Research Results: The results of the service showed that there was a difference in knowledge in the pre-test between the treatment group and the control group (p<0.05), there was no difference in attitudes in the pre-test between the treatment group and the control group (p>0.05), none differences in both knowledge and attitudes before and after in the treatment group (p>0.05), there were no differences in both knowledge and attitudes in the pre-test and post-test in the control group (p>0.05), there were differences in knowledge in the post-test between groups treatment and control groups (p>0.05), there was no difference in attitudes in the post test between the treatment group and the control group (p>0.05). Conclusion: Safety behavior training is effective in increasing the knowledge and attitudes of informal sector workers. Keywords: Knowledge, Attitude, Safety Behavior